A STUDY ON EFFECT OF DIGITAL MARKETING ON CONSUMER BUYING BEHAVIOUR AT CHENGALPATTU DISTRICT TAMILNADU - M.SUBHA; Dr T.S. AARATHY (The Bioscan, 2026)
The method of showcasing orientations to advertising through modern channels such as social media, email announcement, and mobile applications is referred to as digital marketing. This approach allows consumers to explore and evaluate the products offered by various businesses. Thanks to online marketing, shoppers can now access items from around the globe, not just from their own nations. In recent years, companies have embraced eco-friendly merchandising techniques as a means of achieving their corporate goals while conserving environmental resources. This research aims to understand consumer purchasing patterns in relation to digital marketing. Both qualitative and quantitative research methods were utilized in this investigation. Fundamental data was gathered from organized retail stores in Faisalabad. A survey was sent to 150 individuals through Google forms, resulting in 150 qualified responses. The research samples were collected using the Simple Random Sampling Technique. Descriptive statistics, reliability assessment, correlation analysis, and regression analysis were employed to interpret and evaluate the findings for conclusions. Keywords Digital relationship, Digital marketing, Artificial Intelligence, Purchase behavior, Intention.